Supplier Performance Management in Higher Educational Institutions - Hassan, Sallaudin bin; Hajar R, Siti; Firdaus A, Khairul; J, Jimisiah (International Journal of Supply Chain Management, 2016)
Due to diversity of Supply Chain Management (SCM), it could be applied at various industries, including manufacturing and service industries. This paper reveals the Supplier Performance Management activities in the educational institutions, one of the very common sectors in the service industries. This research is significant in view of  the need in ensuring that the supply chain activities at the education sector is aligned with the objective to provide the best service to the stake holders especially the future human capital resource, which  is the graduates. The research has successfully been carried out at University Kuala Lumpur (UniKL) Strategic Business Unit (SBU) or campuses. This research analysed Supplier Performance Management practice between the campuses, criteria used for supplier performance and identify barrier elements in applying supplier performance management. Data collection has been carried out by the primary data, i.e. using questionnaires and interview session. The study revealed significant finding which contributed to the Supply Chain Knowledge and practices. There is a gap between the supplier assessment criteria adopted by the campuses as compared with literature review. There are differences in supplier evaluation criteria between the 7 campuses involved in the research. ISO certification, top management commitment and poor knowledge on benefits of Supplier Performance Management system are barrier factors. The research found variances of supplier evaluation criteria among the campuses. It is suggested to explore further on the connection/relationship between Quality Management System (QMS) or ISO 9001 certified organization and Supplier Performance Management adoption.